Disrupting interaction between miR-132 and Mmp9 3′UTR improves synaptic plasticity and memory in mice - Kuzniewska, Bozena; Rejmak, Karolina; Nowacka, Agata; Ziółkowska, Magdalena; Milek, Jacek; Magnowska, Marta; Gruchota, Jakub; Gewartowska, Olga; Borsuk, Ewa; Salamian, Ahmad; Dziembowski, Andrzej; Radwanska, Kasia; et al. (Frontiers in Molecular Neuroscience, 2022)
As microRNAs have emerged to be important regulators of molecular events occurring at the synapses, the new questions about their regulatory effect on the behavior have araised. In the present study, we show for the first time that the dysregulated specific targeting of miR132 to Mmp9 mRNA in the mouse brain results in the increased level of Mmp9 protein, which affects synaptic plasticity and has an effect on memory formation. Our data points at the importance of complex and precise regulation of the Mmp9 level by miR132 in the brain.